On the H-ring structure of infinite Grassmannians - Lakos, Gyula (Methods of Functional Analysis and Topology, 2010)
The H-ring structure of certain infinite dimensional Grassmannians is discussed using various algebraic and analytical methods but avoiding cellular arguments. These methods allow us to treat these Grassmannians in a greater generality.